The Exoskeleton Hand For Paralysed Fingers: An Overview And Iot Based Application For Practical Example - Hussin, Muhammad Zulhilmi; Jalani, Jamaludin; Sadun, Amirul Syafiq; Wei, David Ting Lung; Mohd Rejab, Sujana (2024)
Restoring finger mobility is crucial for overall movement recovery, particularly for individuals with paralyzed fingers, as fingers are instrumental in grasping and releasing actions. This study begins by providing an overview of the current state of exoskeleton hand technology, highlighting its strengths and weaknesses. Subsequently, it introduces a novel exoskeleton hand with integrated IoT capabilities, focusing on four fingers: the index, middle, ring, and small fingers to address paralysis. The IoT functionality is achieved using the Blynk application, allowing remote control of the exoskeleton hand via a mobile phone. Successful remote-control demonstrations showcase optimal responses during gripping and releasing motions. This study offers an efficient alternative for the rehabilitation process, empowering patients to regain control over their paralyzed fingers.